Relayout of Palm Coconut Factories in West Sumatera - Demi Ramadian; Tosty Maylangi Sitorus (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
One of the plantation companies and palm oil mills in West Sumatera is part of the group and makes a positive contribution. In one of the palm oil factories in West Sumatra, there is a problem with the flow of the work process, where there is an accumulation of products of different sizes in the factory area. This hinders the product transfer process. In addition, this situation will affect the use of the land area. Therefore, it is necessary to consider how to make or change the layout of facilities more effectively and efficiently. An activity Relationship Chart will be used as a method to make recommendations for the layout design of palm coconut factories. The flow of the crude palm oil production process from the proposed layout design weighs the car and bunches of fresh fruits before heading to isolation until the bunches of ripe fruits are stored in the storage tank before being transferred to the transport car. Based on the proposed layout redesign, the management of the oil palm mill can consider improving the placement of the area in the boiler station, as well as the placement of production not too far from the production process.